Hypoxia Induced Factor in Chronic Kidney Disease: Friend or Foe? - Li, Weiying; Zhao, Yuliang; Fu, Ping (Frontiers in Medicine, 2018)
Many studies have shown evidence that Erythropoiesis-Stimulating Agents, as a classic treatment for chronic kidney disease (CKD)-related anemia, have several disadvantages and may trigger various adverse events with long-term use. The Hypoxia-Induced Factor (HIF) pathway has been intensively investigated in kidney disease, especially in CKD, as research has shown that HIF-mediated erythropoiesis might work as a potential therapeutic strategy for managing CKD-related anemia. Development of Prolyl Hydroxylase domain Inhibitors (PHIs), as an effective HIF activator, is a valuable step towards finding a replacement for ESAs, which showed an effective erythropoiesis through a comprehensive and physiological approach by promoting EPO production, increasing iron bioavailability and improving chronic inflammatory status. Heretofore no adverse events or obvious off-target effects have been reported in clinical trials of PHIs. Nevertheless, a cautious inspection with extended follow-up period is warranted to validate the safety of prolonged HIF elevation, especially considering its ambiguous role in fibrogenesis and inflammation responses and possible risks in accelerating vascular calcification and tumorigenesis. A weighed dosing strategy might be the key to circumvent the unexpected side-effect brought by pleotropic effects of HIF elevation and achieve a selective augmentation of HIF-mediated signalling pathway. New studies with longer follow-up period and adequate analysis about the risks for pro-inflammation, vascular calcification and tumorigenesis are needed to ensure the drugs are safe for long-term use before being widely accepted in daily clinical practice.